THE ROLE OF ZAKAT IN THE ECONOMIC EMPOWERMENT OF THE COMMUNITY IN SURABAYA CITY - Fadhil Muhammad Akbar; Siti Kalimah (Institut Agama Islam Negeri (IAIN) Bone, 2025)
Zakat as an Islamic social finance instrument plays a strategic role in transforming socio-economic conditions and reducing poverty in urban areas. This research analyzes the role of zakat in empowering Surabaya City community through productive zakat programs. Methods: This qualitative research uses library research approach. Data were collected from peer-reviewed journals, BAZNAS and LAZNAS reports, and academic books on Islamic economics. Sources were selected using purposive sampling focusing on Surabaya City context. Productive zakat significantly empowers Surabaya's economy through programs like